The influence of tumour blood perfusion variability on thermal damage during nanoparticle-assisted thermal therapy. (18th August 2015) - Soni, Sanjeev; Tyagi, Himanshu; Taylor, Robert A.; Kumar, Amod
Abstract: Purpose : This study investigates the influence of blood perfusion variability within a tumour and the surrounding healthy tissue during nanoparticle-assisted thermal therapy. It seeks to define ideal therapeutic parameters for a wide range of perfusion rates to attain the desired thermal damage. Material and methods : Pennes' bioheat model and the Arrhenius model are used to evaluate the thermal damage for a two-dimensional tumour surrounded by healthy tissue. A wide range of tumour perfusion rates were modelled, ranging from moderate to high perfusion in both a homogenously and a heterogeneously perfused tumour. Results : For low perfusion rates, a temporal variation in blood perfusion does not critically influence the thermal damage. For moderately and highly perfused tumours, temporal variation in blood perfusion extends the thermal damage zone by 25–52% compared to a constant perfusion rate. For the tumour size and perfusion conditions under consideration, the ideal therapeutic parameters were found to be irradiation intensity of 1 W/cm 2, and irradiation duration of 105–150 s, for a nanoparticle volume fraction of 0.001%. Conclusions : It is concluded for low perfusion rates that due to shorter therapeutic duration, nanoparticle-assisted thermal therapy is relatively insensitive to changes in the perfusion rate during the therapy. For moderately and highly perfused tumours, a constant perfusion under-predicts the real thermal damage zone. This study concludes that for moderately and highly perfused tumours the spatial as well as temporal blood perfusion dynamics should be carefully accounted for to get a realistic estimate of thermal damage zone.